STRATEGIES FOR SCALING UP MICRO, SMALL AND MEDIUM ENTERPRISES (UMKM) - Agus Tamrin Reni (Lafadz Jaya Publisher, 2023)
This research aims to find out how to increase the scale of micro, small, and medium enterprises (UMKM) by analyzing the strategies to be used. In this study, using a literature review, data collection was carried out through direct observation and documentation. The analysis technique used by analyzing the business strategies of micro, small, and medium enterprises (UMKM) that have been implemented the results of the analysis of UMKM business strategies are improved by improving the business management of micro, small, and medium enterprises (UMKM) themselves according to several scales that are applied.